2009
DOI: 10.3177/jnsv.55.66
|View full text |Cite
|
Sign up to set email alerts
|

Hypohomocysteinemic Effect of Cysteine Is Associated with Increased Plasma Cysteine Concentration in Rats Fed Diets Low in Protein and Methionine Levels

Abstract: Summary Rats were fed diets with and without 0.5% L -cysteine supplement for 14 d or shorter periods to clarify the mechanism by which dietary cysteine elicits its hypohomocysteinemic effect. Cysteine supplementation significantly decreased plasma homocysteine concentration with an increase in plasma cysteine concentration in rats fed 10% casein diet (10C) or 15% soybean protein diet (15S) but not in rats fed 25% casein diet (25C) or 25% soybean protein diet. Cysteine supplementation also significantly suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
(36 reference statements)
2
12
0
2
Order By: Relevance
“…Another possible reason is that 20CFD, compared with 10CFD, increased or tended to increase the activities of three enzymes that participate in the metabolism of homocysteine. The third possible reason is that plasma cysteine concentration was increased in rats fed 20CFD and thereby reduced plasma homocysteine, because cysteine elicits its hypohomocysteinemic effect through the enhancement of plasma cysteine (42). In any case, the present study suggests that rats fed diets containing higher levels of casein are less susceptible to folate deficiency.…”
Section: Discussionmentioning
confidence: 54%
“…Another possible reason is that 20CFD, compared with 10CFD, increased or tended to increase the activities of three enzymes that participate in the metabolism of homocysteine. The third possible reason is that plasma cysteine concentration was increased in rats fed 20CFD and thereby reduced plasma homocysteine, because cysteine elicits its hypohomocysteinemic effect through the enhancement of plasma cysteine (42). In any case, the present study suggests that rats fed diets containing higher levels of casein are less susceptible to folate deficiency.…”
Section: Discussionmentioning
confidence: 54%
“…These results suggest that the hypohomocysteinemic effect of moderate and high casein diets cannot be ascribed solely to glycineϩ serine contained in casein, although these amino acids surely contribute to the prevention of methionineinduced hyperhomocysteinemia to a considerable degree. In the present study, we did not test the effect of cystine, because the cystine content of casein is very low and cystine did not exhibit a hypohomocysteinemic effect when added to methionine-supplemented diets in rats (30). We recently reported that glutamic acid, histidine, and arginine significantly suppressed methionineinduced hyperhomocysteinemia when added to a methionine-supplemented diet at a level of 2.5%, although the effects of these amino acids were far weaker than those of glycine and serine (31).…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the experiments, all rats were acclimated to the facility for 5 d and given free access to water and a 25% casein diet. In the present study, seven experimental diets (A-G) differing in casein level (10,30, and 50%) and differing in methionine level together with or without glycine ϩ serine supplementation were used (Table 1). These diets were abbreviated as follows:…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Free serine, glycine and cysteine supplements lowered homocysteine concentrations in rodents fed either a low-protein or a high-protein diet (94)(95)(96). The lowering effect of cysteine is associated with increased plasma cysteine concentrations in rodents (97). In apparently healthy humans, concurrent intake of free cysteine and serine can attenuate the rise on postprandial homocysteine concentrations as a result of free methionine (17).…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%